2016
DOI: 10.1159/000449465
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Decay Rate as an Indicator of the Time Interval between Initial Infection and First Diagnosis among Drug-Naïve Human Immunodeficiency Virus Seropositive Individuals in Lagos, Nigeria

Abstract: Objective: The aim of this study was to determine the time interval between human immunodeficiency virus (HIV) infection and the first diagnosis among drug-naïve individuals in Badagry, Nigeria. Subjects and Methods: A sample of 213 subjects who tested HIV positive for the first time were enrolled in this study. The HIV diagnosis was performed using Startpak® and Determine® kits, and a CD4 count was carried out using a FACS Count® flow cytometer. The mean CD4 values were determined by gender and age groups. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…12 A cross-sectional study in Nigeria observed a mean time between HIV infection and diagnosis was 6.7 years and 8.1 years for men and women, respectively. 13 In Nigeria and the United Kingdom, delayed HIV diagnosis is associated with increased mortality and decreased survival time. 14,15 Demographic factors have been described as predictors of delayed HIV diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…12 A cross-sectional study in Nigeria observed a mean time between HIV infection and diagnosis was 6.7 years and 8.1 years for men and women, respectively. 13 In Nigeria and the United Kingdom, delayed HIV diagnosis is associated with increased mortality and decreased survival time. 14,15 Demographic factors have been described as predictors of delayed HIV diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The studies have found that individuals with higher baseline CD4 counts at the initiation of the ARV have the best chance for full immune reconstitution 10 . Furthermore, the baseline CD4 count among the diagnosed PLHIV is important to determine the approximate time of HIV infection to understand whether there is a delay in case of diagnosis since infection and appropriate interventions can be taken to enhance early diagnosis 11 . The delayed HIV diagnosis results in advanced immune compromise, increased risk of treatment failure, 12 loss of opportunities for preventing onward transmission, and ultimately increases costs for the healthcare system 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“… 10 Furthermore, the baseline CD4 count among the diagnosed PLHIV is important to determine the approximate time of HIV infection to understand whether there is a delay in case of diagnosis since infection and appropriate interventions can be taken to enhance early diagnosis. 11 The delayed HIV diagnosis results in advanced immune compromise, increased risk of treatment failure, 12 loss of opportunities for preventing onward transmission, and ultimately increases costs for the healthcare system. 13 , 14 , 15 In many of the countries, HIV cases are diagnosed very late thus resulting in high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%